Swear Words in “End of Watch” Movie Directed by David Ayer (A Socio-Pragmatics Study) - Sabanti, Mayanti A.; Malabar, Fahria; Bouti, Suleman (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The purpose of this study is to examine the swear words uttered by all of the characters in the "End of Watch" film using a socio-pragmatics approach. Swear words are harsh words used by people to express their emotions, such as anger, impatience, joy, despair, and so forth. The qualitative method was used to conduct this research. In this study, the data were gathered by watching the movie, then selecting, classifying, analyzing, and describing the utterances that contain swear words utilizing the note-taking technique. The gathered data are then analyzed by using the following procedures: prepare the data for analysis, read and interpret the data, categorize and describe the data, re-watch the movie, present the findings and analyze the data, and draw conclusions. The data of this study were evaluated using Andersson and Trudgill's theory of swear word types, as well as Staley's theory of factors that cause characters to use swear words. The data analysis revealed that there were 34 data containing four categories of swear words used by all of the characters in the film "End of Watch," with several causal factors. There were 14 data include in expletive swearing with 9 factors, 16 in abusive swearing with 10 factors, 2 in humorous swearing with 2 factors, and 2 in auxiliary swearing without any factors influencing them. According to the data, expletive and abusive swearing were the most commonly used categories in this film, with a variety of causes contributing to characters utilizing swear words. The least common forms were humorous and auxiliary swearing. In conclusion, the findings suggest that the characters in the film used swear words to communicate their emotions, with expletive and abusive swearing being the primary means of expression.